2018
DOI: 10.1021/acs.jmedchem.8b00277
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of an Acyl Migration Prodrug Strategy with Bio-activation To Improve Oral Delivery of the HIV-1 Protease Inhibitor Atazanavir

Abstract: HIV-1 protease inhibitors (PIs), which include atazanavir (ATV, 1), remain important medicines to treat HIV-1 infection. However, they are characterized by poor oral bioavailability and a need for boosting with a pharmacokinetic enhancer, which results in additional drug-drug interactions that are sometimes difficult to manage. We investigated a chemo-activated, acyl migration-based prodrug design approach to improve the pharmacokinetic profile of 1 but failed to obtain improved oral bioavailability over dosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 40 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…The N7 / N9 -transferrocenoylation in purines may be classified as an intramolecular acyl migration, which is of special importance in organic and medicinal chemistry. An acyl shift occurs frequently in carbohydrates, lipids, or peptides and serves as a reaction channel in prodrug design and various synthetic strategies. So far, however, only a few studies have coupled experimental and computational methods to clarify the underlying mechanism. In this work, a cluster of earlier relevant examples, including imidazole rings and benzotriazoles, , has been expanded to purines.…”
Section: Introductionmentioning
confidence: 99%
“…The N7 / N9 -transferrocenoylation in purines may be classified as an intramolecular acyl migration, which is of special importance in organic and medicinal chemistry. An acyl shift occurs frequently in carbohydrates, lipids, or peptides and serves as a reaction channel in prodrug design and various synthetic strategies. So far, however, only a few studies have coupled experimental and computational methods to clarify the underlying mechanism. In this work, a cluster of earlier relevant examples, including imidazole rings and benzotriazoles, , has been expanded to purines.…”
Section: Introductionmentioning
confidence: 99%
“…More recently,S ubbaiah et al reported their work on improving the oral bioavailability of Atazanavir;a nH IV-1 PR inhibitor (Scheme 2D). [36] This isoacyl prodrug was prepared with a capped isoacyl motif. An esterase-mediated removal of the valine triggered the subsequent releaseo fi sobutyric aldehyde and carbon dioxide, and eventually the free isoacyl motif, which simultaneously underwent the O-to-N acyl shift to provide Atazanavir.…”
Section: Applicationo Fi Soacyl Structural Motifs In Prodrug Designmentioning
confidence: 99%
“…More recently, Subbaiah et al. reported their work on improving the oral bioavailability of Atazanavir; an HIV‐1 PR inhibitor (Scheme D) . This isoacyl prodrug was prepared with a capped isoacyl motif.…”
Section: Application Of Isoacyl Structural Motifs In Prodrug Designmentioning
confidence: 99%
“…While such prodrug approaches were previously explored in attempts to improve absorption, distribution, metabolism and drug excretion (ADME) none have yet to be applied to the generation of reservoir targeted LA DRV (30)(31)(32)(33). Prior efforts included, but were not limited to, carrier-mediated drug delivery approaches that incorporate amino acids to minimize p-glycoprotein efflux and mitigate first pass metabolism (30,34). Notably, extensive prodrug approaches have led to development and approval of fosamprenavir, a phosphorylated water-soluble prodrug of amprenavir (35).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy is utilizing prodrugs to extend the half-life and biodistribution of the agent. While such prodrug approaches were previously explored in attempts to improve absorption, distribution, metabolism, and drug excretion (ADME), none have yet to be applied to the generation of reservoir-targeted LA DRV. Prior efforts included, but were not limited to, carrier-mediated drug delivery approaches that incorporate amino acids to minimize p-glycoprotein efflux and mitigate first pass metabolism. , Notably, extensive prodrug approaches have led to development and approval of fosamprenavir, a phosphorylated water-soluble prodrug of amprenavir . Various fatty ester prodrugs of indinavir and saquinavir have been described but are significantly less potent compared to the parent drugs .…”
Section: Introductionmentioning
confidence: 99%